2015
DOI: 10.1590/s0036-46652015000700007
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis Treatment

Abstract: SUMMARYConsidered to be an emerging endemic mycosis in Latin America, paracoccidioidomycosis is characterized by a chronic course and involvement of multiple organs in immunocompromised hosts. Infection sequelae are mainly related to pulmonary and adrenal insufficiency. The host-parasite interaction results in different expressions of the immune response depending on parasite pathogenicity, fungal load and genetic characteristics of the host. A few controlled and case series reports have shown that azoles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 46 publications
(47 reference statements)
1
50
0
8
Order By: Relevance
“…Moreover, FAMEs (soybean, corn and sunflower) showed better activity than SMX-THT (P = 0.0001) against the isolates of P. brasiliensis Pb-18, Pb-608, Pb-1017, Pb-9673 and P. lutzii 01. SMX-THT is used in the treatment of PCM, mainly in endemic regions where other therapy (such as itraconazole) is not easily available; consequently, therapy consisting of SMX-THT is a useful option (de Oliveira et al 2015, Shikanai-Yasuda 2015. The difference in antifungal activity between different FAMEs, against 11 isolates of Paracoccidioides spp., is not statistically significant (P < 0.05).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Moreover, FAMEs (soybean, corn and sunflower) showed better activity than SMX-THT (P = 0.0001) against the isolates of P. brasiliensis Pb-18, Pb-608, Pb-1017, Pb-9673 and P. lutzii 01. SMX-THT is used in the treatment of PCM, mainly in endemic regions where other therapy (such as itraconazole) is not easily available; consequently, therapy consisting of SMX-THT is a useful option (de Oliveira et al 2015, Shikanai-Yasuda 2015. The difference in antifungal activity between different FAMEs, against 11 isolates of Paracoccidioides spp., is not statistically significant (P < 0.05).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The treatment comprises addition of antifungal agents and the use of measures to improve the general condition of the patient. Some controlled studies and case series have shown that azoles fast action and sulfa derivatives are useful therapeutic options for milder forms of the disease while in moderate/severe cases, longer treatments or parenterally are needed, especially when there is mucosal involvement …”
Section: Introductionmentioning
confidence: 99%
“…Some controlled studies and case series have shown that azoles fast action and sulfa derivatives are useful therapeutic options for milder forms of the disease while in moderate/severe cases, longer treatments or parenterally are needed, especially when there is mucosal involvement. 9 The epidemiological approach to PCM is difficult, since its notification is not compulsory. The prevalence calculations, incidence and morbidity are based on reports of epidemiological studies and case series.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodimorphic fungi of the Paracoccidioides genus cause paracoccidioidomycosis (PCM), an endemic granulomatous mycosis of the sub-tropical regions of Latin America, widespread from south of Mexico to north of Argentina, with a high prevalence in South America [120][121][122][123]. PCM generally affects male workers in close contact with the soil in rural areas.…”
Section: Paracoccidioides Sppmentioning
confidence: 99%